Essays on the competitiveness and export performance of African economies - (:unkn) unknown (My University, 2024)
With a population of over 1.4 billion, making Africa the world's second most populous continent after Asia, its contribution to world trade remains modest. Economic literature identifies several factors contributing to the marginalization of African nations in world trade, including a lack of competitiveness. Drawing on the existing literature, and recognizing that there is no universal solution, this thesis explores, in three chapters, the ways in which price and non-price competitiveness can help African nations to integrate more fully into world trade. The first chapter looks at the measurement of price competitiveness, specifically examining the competitiveness of the CFA franc through the prism of the behavioral equilibrium exchange rate (BEER) and purchasing power parity (PPP). One notable contribution is the inclusion of natural rents, which are particularly important in African countries. The results highlight disparities between monetary unions (WAEMU and CEMAC), sub-periods and countries considered. Analysis of the results at the end of the 2014-2016 period does not call for a readjustment of parity. The second chapter explores the impact of undervalued exchange rates on the occurrence of episodes of accelerated growth in exports of African products. The analysis encompasses a variety of key export products, both primary and manufactured, with a unique microeconomic approach tailored to each product. Over the period 1995-2017, 96 episodes are identified for 41 African countries. Estimates confirm that undervaluation significantly stimulates growth surges in African export products. The third and final chapter focuses on non-price competitiveness, exploring the implications of the rapid deployment of submarine cables along African coasts for the sophistication of African countries' export baskets. Based on a sample of developing countries, including 23 Sub-Saharan African countries over the period 1995-2017, the results indicate that digital
Keywords: African Research